Hybrid Sampling: Menjembatani Representativitas dan Fleksibilitas dalam Penelitian Kontemporer - Taharuddin (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: Sample selection is a crucial component of research methodology because it determines the extent to which results can be generalized and justified. However, both probability and non-probability sampling have their limitations. Probability sampling excels at generating representative data but requires large costs and a complete sampling frame. Conversely, non-probability sampling is more flexible and resource-efficient but is often questioned for its validity and objectivity. Hybrid sampling emerges as a methodological strategy that combines the strengths of various sampling techniques to minimize their respective weaknesses. This article aims to examine the concept, urgency, and implications of hybrid sampling in contemporary research. The writing is conducted with a systematic literature review (SLR) approach to classical and contemporary methodological literature. The results of the study show that hybrid sampling is able to address population complexity, cost and time efficiency, and the need to balance generalization and depth of information. Its theoretical implication lies in expanding a more adaptive research methodology paradigm, while its practical implications are relevant for academic researchers and practitioners in social, health, and marketing fields. Thus, hybrid sampling is not just an alternative but an increasingly relevant methodological strategy in the modern research era